Attention deficit hyperactivity disorder in male patients with alcohol dependence - Etik, Ç.; Taner, Y.; Taner, E.; Arıkan, Z. (Journal of Dependence, 2008)
Objective: This study aimed to investigate the symptoms of Attention Deficit Hyperactivity Disorder (ADHD) in adulthood and childhood in patients with adult alcohol dependence and to examine the sociodemographic and clinical characteristics of these cases. Method: The study included 54 patients diagnosed with alcohol dependence who were currently undergoing treatment and those who had previously received treatment and were being followed up as outpatients. ADHD was diagnosed using the Turgay Adult ADHD Diagnostic and Assessment Scale based on DSM-IV. The Wender Utah Rating Scale was used to screen for childhood ADHD symptoms. Findings: After individuals were divided into two groups according to the presence of ADHD, the mean age at onset of alcohol use (p
Keywords: Attention Deficit Hyperactivity Disorder; adult; alcohol dependence